A Study on the Growth and Development Agricultural Library of Ministry of Agriculture and Farmers Welfare in India - Kimi (Journal of Agricultural Extension Management, 2021)
In the present study, the author has investigated the status of the library under the Ministry of Agriculture and Farmers Welfare (MoAFW) to know its resources, services, budget, level of automation for the period 2010-19 with the help of a structured questionnaire designed for the purpose. The author has also interviewed the library's Head and practically observed the status of the library. The findings show that the library is on a steady path for its development, as observed through increased collection, services, and library management areas. This study shall be helpful for the library in designing its roadmap for future developmental processes. Simultaneously, it will help the researchers understand these unique libraries due to their type of collection.